2021
DOI: 10.3389/fnins.2021.685715
|View full text |Cite
|
Sign up to set email alerts
|

Electroacupuncture Regulates Pain Transition Through Inhibiting PKCε and TRPV1 Expression in Dorsal Root Ganglion

Abstract: Many cases of acute pain can be resolved with few side effects. However, some cases of acute pain may persist beyond the time required for tissue injury recovery and transit to chronic pain, which is hard to treat. The mechanisms underlying pain transition are not entirely understood, and treatment strategies are lacking. In this study, the hyperalgesic priming model was established on rats to study pain transition by injection of carrageenan (Car) and prostaglandin E2 (PGE2). The expression levels of protein … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 56 publications
0
12
0
Order By: Relevance
“…Previous studies have demonstrated that PKCε activation in the DRG is a molecular marker of pain transition initiation (Wang et al, 2021). Our previous studies also showed that inhibition of high PKCε expression reverses chronic pain in HP model rats (Fang et al, 2021). Here, we tested whether blocking the induction of SGC reactivity affects PKCε expression in the L5 DRG.…”
Section: Resultsmentioning
confidence: 89%
See 3 more Smart Citations
“…Previous studies have demonstrated that PKCε activation in the DRG is a molecular marker of pain transition initiation (Wang et al, 2021). Our previous studies also showed that inhibition of high PKCε expression reverses chronic pain in HP model rats (Fang et al, 2021). Here, we tested whether blocking the induction of SGC reactivity affects PKCε expression in the L5 DRG.…”
Section: Resultsmentioning
confidence: 89%
“…Fc injection also decreased the expression level of PKCε, as well as GFAP, in the DRG in this study. Our previous research demonstrated that preventing PKCε activation in the lumbar DRG regulates pain transition ( Fang et al, 2021 ). All of the above results indicate that SGC activation is involved in the transition from acute to chronic pain.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Many works of literature have reported that the efficacy of acupuncture is related to the C-type fibers innervating acupoints or DRG neurons expressing TRPV1 ( Wang et al, 1996 ; Tjen et al, 2005 ; Qin et al, 2014 ; Gao X. et al, 2015 ; Chen et al, 2018 ; Guo et al, 2018 ; Liu et al, 2018 ; Li et al, 2019 ; Du et al, 2021 ; Fang et al, 2021 ; Song et al, 2021 ). However, the TRPV1-expressing shared DRG neurons in this study are unlikely to be involved in the analgesia produced by acupuncture at the ST36 acupoint.…”
Section: Discussionmentioning
confidence: 99%